Stereotypes, prejudices, self and ‘the other’ in history textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article is a literature review of conceptions of stereotype, prejudice, underlying assumptions and images of self and other as relevant to historytextbooks and related research. History textbooks are seen as representations of a nation’s o"cial history as they build identity and form conceptions ofmorality in their readers. I address questions like, what are the underlying assumptions of history texts that lead to picturing ourselves and others? Couldan understanding of the other be seen as a liability, given the moral responsibility it introduces? In seeking answers, instead of a sociological approach analysing the social systems of power and oppression, the perpetuating of stereotypes is viewed from an individual, psychological perspective. Hence, I ask how the psychology of hatred could be understood and what this implies for viewing the self in relation to the other through history education. I conclude bystressing that moral responsibility starts with the self and not with the other; and that the bigger enemy of history teaching is not prejudice and stereotype contained in pedagogic texts, but indifference or bystander behaviour that such texts could encourage.
Keywords: Identity; Prejudice; History textbooks; Stereotype; Underlying assumptions; Moral responsibility; Psychology of hatred